Pengaruh Perencanaan Anggaran Dan Manajemen Resiko Terhadap Penyerapan Anggaran Di Desa Bojong Koneng Kecamatan Babakan Madang Kabupaten Bogor - Hendra; Dony Hendartho (Jurnal Ilmu Administrasi Publik, 2026)
Budget absorption in Bojong Koneng Village, Babakan Madang Subdistrict, Bogor Regency, remains suboptimal. The objective of this study is to analyze budget absorption in Bojong Koneng Village, Babakan Madang Subdistrict, Bogor Regency, which remains suboptimal, both partially and simultaneously. This study used an explanatory research method with a quantitative descriptive approach. The study population consists of all village officials in Bojong Koneng Village, totaling 15 employees, 21 RT heads, and 6 RW heads, for a total of 42 respondents. The sampling technique used a census, specifically a complete census, resulting in 42 samples from the entire population. The research results indicate: (1) The magnitude of the influence of budget planning on budget absorption in Bojong Koneng Village, Babakan Madang Subdistrict, Bogor Regency, is 57.3%. (2) The magnitude of the influence of risk management on budget absorption in Bojong Koneng Village, Babakan Madang Subdistrict, Bogor Regency, is 73.3%. (3) The combined effect of Budget Planning and Risk Management on Budget Absorption in Bojong Koneng Village, Babakan Madang Subdistrict, Bogor Regency is 76%.